2013
DOI: 10.1097/dcr.0b013e3182a4b236
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Is Associated With Improved Pathologic Response to Neoadjuvant Chemoradiation in Rectal Cancer

Abstract: Statin therapy is associated with an improved response of rectal cancer to neoadjuvant chemoradiation. These data provide the foundation for a prospective clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…Numerous studies and meta-analysis have investigated whether statin use reduces the risk of developing CRC [14], [15]. Fewer studies focus on effects of statin after diagnosis during treatment [16][21]. The study of Mace et al [16] showed that rectal cancer patients in the statin cohort treated with neo-adjuvant chemoradiation had a better response (65.7% versus 48.7%, p = 0.004) and lower median regression rate (1 versus 2, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies and meta-analysis have investigated whether statin use reduces the risk of developing CRC [14], [15]. Fewer studies focus on effects of statin after diagnosis during treatment [16][21]. The study of Mace et al [16] showed that rectal cancer patients in the statin cohort treated with neo-adjuvant chemoradiation had a better response (65.7% versus 48.7%, p = 0.004) and lower median regression rate (1 versus 2, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies focus on effects of statin after diagnosis during treatment [16][21]. The study of Mace et al [16] showed that rectal cancer patients in the statin cohort treated with neo-adjuvant chemoradiation had a better response (65.7% versus 48.7%, p = 0.004) and lower median regression rate (1 versus 2, p = 0.01). Two other studies [19], [20] in patients with rectal cancer treated with neo-adjuvant chemoradiation showed similar results indicating an association between statin use and response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HMGCR may serve as a predictive marker of response to postoperative radiotherapy in ductal carcinoma in situ (dCIS) (83). A retrospective cohort study suggested an association between statin therapy and improvement in response of rectal cancer to neoadjuvant chemoradiation (84).…”
Section: Synergism Of Statins With Radiotherapy and Chemotherapymentioning
confidence: 99%
“…Patients in the statin cohort showed a better response than those not taking a statin (65.7 vs. 48.7 %, p = 0.004). The authors suggested that statin therapy was associated with an improved response to neoadjuvant therapy in rectal cancer [48].…”
Section: Metabolic Biomarkers As Risk and Prognostic Factors In Crcmentioning
confidence: 99%